Pemberdayaan Perempuan dalam Implementasi Undang-undang No. 6 Tahun 2016 di Desa Lerep, Kabupaten Semarang - Laila Alfirdaus; Kushandajani Kushandajani (Sekolah Vokasi Universitas Diponegoro, 2021)
Although gender problems in village have been obvious, the issuance of Law No. 6/2014 does not automatically transform gender relations in village. As a matter of fact, the Law has clearly asserted woman representation in village decision making and development. Therefore, it is important to strengthen woman awareness of their rights. This article is a reflection of community engagement activities in Lerep, Semarang district, Central Java supported with data from observation, document reviews and interviews prior, during and after the activities. From the data, we can see that teh main challenge for woman empowerment in village come from the facts thatvillage government still prioritizes infrastructure in its development. Development programs that have direct impact on women are limited. On the other hand, women in the village are not yet aware of their rights guaranteed by village law. Information dissemination on woman rights in village decision making and development therefore becomes the initial strategy that is unavoidably needed.